Stroke : selected topics - Bogousslavsky, Julien (World Federation of Neurology seminars in clinical neurology, 2006)
Annotation This volume is the fourth in a series developed under the auspices of the World Federation of Neurology to meet the needs of neurologists who must practice medicine without many of the advantages that are often taken for granted in the industrialized world. It is targeted to neurologists practicing in low-resource environments and those who wish to practice cost-effective neurology. This guide provides a practical review of stroke, a common disabling medical condition. It emphasizes evaluation and treatment and provides advice on how to apply current knowledge in clinical practice. A range of topics are covered, including: # The epidemiology of stroke # Stroke subtypes and rationale for their separation # Recovery and rehabilitation # Stroke in developing countries.